2016
DOI: 10.21649/akemu.v9i1.1322
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Internal Sphincterotomy for Chronic Anal Fissure under local anesthesia as a Day Case Surgery

Abstract: This prospective study was carried out in East Surgical unit, Mayo Hospital, Lahore for the period of two years from July 2001 to July 2002 on outpatient basis. Total of 50 patients aged between 20-50 years fulfilled the criteria of day case surgery i.e., health and social criteria (ASAI&II), only those were included in the study. The objectives were to evaluate the role of lateral sphicnterotomy under local anaesthesia as a day case surgery, considerable cost to patient and hospital, less morbidity and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Conservative LIS under local anesthesia was found effective in more than 98% of patients 14 . Incontinence to flatus was seen in only one patient and no patients developed fecal incontinence 17 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Conservative LIS under local anesthesia was found effective in more than 98% of patients 14 . Incontinence to flatus was seen in only one patient and no patients developed fecal incontinence 17 .…”
Section: Discussionmentioning
confidence: 95%
“…LIS is a gold standard treatment for anal fissure 12 . It is also safely effective in treating CAF 12,14 . In a study it was shown that only 4% of the patients initially healed with 0.2% GTN and had to undergo sphincterotomy for recurrences 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The patients were operated as a daycare procedure using local anaesthesia. With the exception of 1 (2%) patient, all the patients 49 (98%) had sudden pain relief and passed first stool after surgery without pain 20 .…”
Section: Discussionmentioning
confidence: 96%